Wet gas metering performance using conventional flow measurement devices - Mwinyi, Vitalis (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The demand for and production of natural wet gas from wells has significantly risen in recent years. Although natural gas liquids hold substantial value in the oil and gas market, their presence in wet gas adversely affects gas metering, leading to overreading during measurement. A comprehensive study has been undertaken to formulate and enhance correlations for rectifying overreading in wet gas metering. Nevertheless, most current correlations are designed for horizontal configurations of traditional meters. Mitigating this constraint is crucial to consider the impact of gravity on pressure loss in vertically oriented systems. This study seeks to evaluate the efficacy of wet gas overreading correlations utilizing a vertically positioned Venturi flow meter, a recognized instrument for single-phase flow measurement. This project innovatively examines the influence of liquid film formation and flow along the walls of the pressure measurement zone within the Venturi tube. This liquid coating influences differential pressure, and its influence on wet gas overreading correction will be examined using established correlations.